Pengaruh Tandem Walking Exercise Terhadap Keseimbangan Dinamis Pada Lansia Usia 60-74 Tahun - Algazali, Mohamad Asegaf, Yulisna Mutia Sari, SSt.Ft. M.Sc (GRS) (2016)
Background: Elderly an advanced stage of a process of a life marked by a decrease in the body's ability to adapt to environmental stress and not a disease . The aging process will look at the age of 45 years and a problem arises at the age of 60 years . In the elderly will be a decrease of various organs, functions and body systems that are natural , or physiological . The decrease was due to a reduced number of cells and the ability of the body ( Pujiastuti, 2005). A decrease in the body's ability to aging potential occurrence of balance disorders Tandem walking) is an exercise that is done with how to narrow the broad field of fulcrum , by walking in a straight line in a heel position of the foot touches the other toes , this exercise is expected to function dynamically improve postural balance. Talkowski (2008 ). Objective: To determine the effect of exercise walking tandem on a dynamic balance in elderly age of 60-74 years. Methods: The study of this research is Quasi Experiment research or appearance experimental. The Desain of this research is pre and post test two group design compared between the two groups: the treatment group were given tandem walking exercise for 4 weeks, 3 times training a week. Measuring equipment for time up go test. Data were analyzed using the Wilcoxon signed rank test to test the effect and influence of different test using Man Whitney test. Results: There is an effect of the tandem walking exercise on the balance of elderly people aged 60-74 years after the statistical test using Wilcoxon test showed Based on the test results on the effect of exercise tandem walking exercise to increase the dynamic balance of the elderly showed that the value of significance ( p ) = 0.007 or 0.007 < 0 , 05 , exercise walking tandem to increase the dynamic balance of elderly people in the treatment group and the control group showed a value of significance ( p ) = 1.000 or 1.000 > 0.05. Man Whitney test results showed that the value z is -3.749 to 0.000 p-value < 0.05. Conclusion: There is the influence of the tandem walking exercise to the dynamic balance of elderly people aged 60-74 years.